Structural organization and morphometric parameters the inferior olivary complex in the prenatal period of human ontogenesis - V.O. Tyholaz (Danylo Halytsky Lviv National Medical University, 2016)
Aim. To determine the structure and morphometric parameters of the inferior olivary complex nuclei and nerve cells forming it in embryos and human fetuses at different gestational age.